2015
DOI: 10.1597/14-178
|View full text |Cite
|
Sign up to set email alerts
|

“It Doesn't All Just Stop at 18”: Psychological Adjustment and Support Needs of Adults Born with Cleft Lip and/or Palate

Abstract: Adults with CL/P may require psychological support, information about the heritability of cleft, signposting and referrals from nonspecialists, support regarding further treatment, and opportunities to take part in research and activities. New issues arising in adulthood, such as entering the workplace, forming long-term relationships, and starting a family, may warrant both further investigation and additional support. Further work is needed to identify the factors that contribute to psychological distress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(135 citation statements)
references
References 76 publications
6
124
3
2
Order By: Relevance
“…Cleft patients have reported that they have been teased because of their facial anomaly [10][11][12]. In contrast, a recent study found that adults born with a cleft do not report a relevant effect of their facial malformation on social and romantic relationships [13].…”
Section: Introductionmentioning
confidence: 99%
“…Cleft patients have reported that they have been teased because of their facial anomaly [10][11][12]. In contrast, a recent study found that adults born with a cleft do not report a relevant effect of their facial malformation on social and romantic relationships [13].…”
Section: Introductionmentioning
confidence: 99%
“…First, the participant was invited to tell their story of living with CLP. Second, the topic guide was used to furHowever, despite access to this multidisciplinary approach to treatment individuals born with CLP may face ongoing issues in adulthood that impact on self-confidence, inter-personal relationships, and achievement in education and employment [8][9][10][11]. The ongoing impact of living with CLP may, in part, be a function of dissatisfaction with treatment or unmet aesthetic or functional needs.…”
Section: Methods Proceduresmentioning
confidence: 99%
“…However, one recent qualitative study with 52 adults born with CLP found that some participants questioned the value and necessity of ongoing treatment. They suggested that decision-making was influenced by other peoples' opinions about their appearance and function and consequently led to the exacerbation of confusion and distress [8]. Furthermore, individuals born with CLP may also experience positive psychological growth and wellbeing.…”
Section: Methods Proceduresmentioning
confidence: 99%
See 2 more Smart Citations